MODURATORY EFFECT OF THAI TRADITIONAL MEDICINE (YAHOM TULTAVAI) ON HEPATIC CYTOCHROME P450 ENZYMES AND PENTOBARBITAL-INDUCED SLEEPING IN MICE - Sirisangtragul, Wanna; Sripanidkulchai, Bungorn (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Yahom Tultavai is a Thai traditional medicine that has been widely used in the aged-people for the treatment of nausea, vomiting, dizziness and weakness. It formula contains several medicinal plants and one of them is Kaempferia galanga L., that has ethyl-p-methoxycinnamate (EPMC) as its major compound. Recently, several herbs and traditional medicines have been reported to demonstrate herbal-drug interaction with conventional medicines. This study aims to investigate the effect of Yahom Tultavai extracts on hepatic cytochrome P450 enzymes and pentobarbital-induced sleeping in mice. Three extracts of Yahom Tultavai, using dichloromethane, methanol and distilled water as solvents were orally administered for 28 days prior to determine CYP1A1, CYP1A2, CYP2B, CYP2E1 and CYP3A4 activities. All three extracts significantly inhibited CYP1A1, CYP1A2 and CYP 2E1 activities, but only dichloromethane extract enhanced CYP2B activity. In addition, all three extracts had no effect on CYP3A4 activity. As an indicator for metabolic drug interaction, pentobarbital–induced sleeping time was decreased in connection to the induction of CYP2B activity in 7 and 28 days of dichloromethane extract and EPMC-treated animals when compared to control. In conclusion, Yahom Tultavai extracts affected hepatic microsomal CYP enzyme activities and reduced pentobarbital-induced sleeping time in mice. The results suggest that Yahom Tultavai may potentially cause herbal and conventional drug interaction, which can affect the clinical implication of drug action. Therefore, the co-administration of Yahom Tultavai with certain drugs should be carefully considered.